Characterization of a novel thermotolerant NAD+-dependent formate dehydrogenase from hot climate plant cotton (Gossypium hirsutum L.) - Kurt-Gur, Gunseli; Ordu, Emel (SPRINGER HEIDELBERG, 2018)
NAD+-dependent formate dehydrogenases (FDH, EC 1.2.1.2), providing energy to the cell in methylotrophic microorganisms, are stress proteins in higher plants and the level of FDH expression increases under several abiotic and biotic stress conditions. They are biotechnologically important enzymes in NAD(P)H regeneration as well as CO2 reduction. Here, the truncated form of the Gossypium hirsutum fdh1 cDNA was cloned into pQE-2 vector, and overexpressed in Escherichia coli DH5 alpha-T1 cells. Recombinant GhFDH1 was purified 26.3-fold with a yield of 87.3%. Optimum activity was observed at pH 7.0, when substrate is formate. Kinetic analyses suggest that GhFDH1 has considerably high affinity to formate (0.76 +/- 0.07 mM) and NAD+ (0.06 +/- 0.01 mM). At the same time, the affinity (1.98 +/- 0.4 mM) and catalytic efficiency (0.0041) values of the enzyme for NADP(+) show that GhFDH1 is a valuable enzyme for protein engineering studies that is trying to change the coenzyme preference from NAD to NADP which has a much higher cost than that of NAD. Improving the NADP specificity is important for NADPH regeneration which is an important coenzyme used in many biotechnological production processes. The Tm value of GhFDH1 is 53.3 degrees C and the highest enzyme activity is measured at 30 degrees C with a half-life of 61 h. Whilst further improvements are still required, the obtained results show that GhFDH1 is a promising enzyme for NAD(P) H regeneration for its prominent thermostability and NADP(+) specificity.
Keywords: Coenzyme regeneration; Gossypium hirsutum; Formate dehydrogenase; NADP(+) specificity; Thermostability; THERMAL-STABILITY; COENZYME SPECIFICITY; EFFICIENT; PURIFICATION; REDUCTION; TOLERANCE; CLONING; CO2; Biotechnology & Applied Microbiology